Effect of Origanum onites L. Essential Oil and Cold Atmospheric Plasma on Physicochemical, Microbial, and Sensory Properties of Iranian White Cheese - Razie Razavi; Ehsan Toosi; Mahjoub Sheikholeslami; Maryam Konjedi; Adel Hajian-Tilaki; Ali Najafi (Journal of Food Quality)
This study investigated into the antioxidant and antimicrobial properties of Origanum onites essential oil (OEO) and the application of cold atmospheric plasma (CAP) on Iranian white cheese quality during storage at 4°C for 45 days. OEO contains 28.43 ± 0.34 mg GAE/g dw and exhibited antioxidant and antimicrobial activity in in vitro tests. Iranian white cheese inoculated with Escherichia coli, Listeria monocytogenes, Salmonella typhimurium, and Staphylococcus aureus followed by the addition of OEO at two concentrations of 2000 and 3000 ppm, and then treated by CAP for 3 and 7 min. Samples were stored at 4°C. pH, thiobarbituric acid value (TBA), L∗, a∗, b∗ color indexes, microbial count, and sensory properties of cheese samples were evaluated on days 0, 7, 15, 30, and 45. The pH value, L∗, a∗, b∗ indexes and sensorial properties of all samples decreased over time, while the TBA value and bacterial count increased. The physiochemical, microbial, and sensorial findings suggested that a combination of OEO (2500 ppm) and CAP (3 min) could be helpful in the induction of microbial growth and oxidative reactions in Iranian white cheese.